Spark Plasma Sintering of Lithium Aluminum Germanium Phosphate Solid Electrolyte and its Electrochemical Properties - Hongzheng Zhu (Nanomaterials, 2019)
Sodium superionic conductor (NASICON)-type lithium aluminum germanium phosphate (LAGP) has attracted increasing attention as a solid electrolyte for all-solid-state lithium-ion batteries (ASSLIBs), due to the good ionic conductivity and highly stable interface with Li metal. However, it still remains challenging to achieve high density and good ionic conductivity in LAGP pellets by using conventional sintering methods, because they required high temperatures (>800 °C) and long sintering time (>6 h), which could cause the loss of lithium, the formation of impurity phases, and thus the reduction of ionic conductivity. Herein, we report the utilization of a spark plasma sintering (SPS) method to synthesize LAGP pellets with a density of 3.477 g cm−3, a relative high density up to 97.6%, and a good ionic conductivity of 3.29 × 10−4 S cm−1. In contrast to the dry-pressing process followed with high-temperature annealing, the optimized SPS process only required a low operating temperature of 650 °C and short sintering time of 10 min. Despite the least energy and short time consumption, the SPS approach could still achieve LAGP pellets with high density, little voids and cracks, intimate grain−grain boundary, and high ionic conductivity. These advantages suggest the great potential of SPS as a fabrication technique for preparing solid electrolytes and composite electrodes used in ASSLIBs.